Groynes in riverbank erosion control: an integrated hydrodynamic and morphodynamic modelling for a selected reach of the Padma river - Shahariar, Shadman; Sultana, Nahid; Zobeyer, Hasan (Environmental earth sciences, 2025)
The Padma River, a highly dynamic system characterized by intense bank erosion and rapid morphological changes, presents significant challenges to riverbank stability and infrastructure. Despite the widespread use of groyne-type structures for riverbank protection, their performance under varying configurations in such dynamic environments remains under-explored. Therefore, this study contributes to the advancement of existing knowledge by quantitatively analyzing the performance of multiple groyne configurations under varying flood scenarios using a high-resolution hydro-morphological modeling approach. Historical planform analysis indicates severe bank retreat, with 1,510 m of erosion recorded between 1988 and 1993 and 810 m between 2018 and 2023, driven by increased meandering and higher sinuosity. A high-resolution Delft3D Domain Decomposition (DD) model was developed through a sensitivity analysis and calibrated using 2018 monsoon (June–September) data at Mawa station, achieving very good accuracy in both water level and discharge simulations. Simulations are undertaken to assess the effectiveness of groyne interventions under 10-, 50-, and 100-year flood events. Four simulation scenarios were tested: a base condition without groynes and three alternative configurations featuring three, four, and seven groynes installed across erosion-prone zones. Analysis of the simulation results revealed that the configuration with seven groynes effectively redirected high-velocity flows away from vulnerable banks, substantially reducing near-bank velocities and bed shear stresses, and minimizing riverbed scour depths during extreme events. The findings underscore the critical importance of optimized groyne placement for enhancing riverbank stability in dynamic river systems subject to intensified climate-driven flood risks.